Equity in awareness and utilization of cervical cancer screening services among women of reproductive age in Uganda: Analysis of vertical equity using evidence from UDHS 2022 - Geofrey Emesu; Elizabeth Ekirapa Kiracho; Alfred Jatho; Joseph Kagaayi; Aggrey David Mukose; Annette Kyomuhangi (PLoS ONE, 2026)
Background Cervical cancer poses a severe public health burden in Uganda, which has one of the world’s highest incidence rates. Despite commitments to Universal Health Coverage (UHC), screening utilization remains critically low and inequitable. This study assessed vertical equity in the awareness and utilization of cervical cancer screening services among women in Uganda, evaluating whether distribution aligns with differential need. Methods We conducted a cross-sectional analysis of the 2022 Uganda Demographic and Health Survey (UDHS), including 18,251 women aged 15–49. The primary outcomes were self-reported screening utilization and awareness. Socioeconomic status was measured using the DHS wealth index. Equity was assessed using concentration curves and indices (CIs), with a positive CI indicating pro-rich inequality. P.value of 0.05 (95% confidence interval) was used to test for significance of study findings. Results We found significant pro-rich inequity in both screening utilization (CI = 0.125, p < 0.000) and awareness (CI = 0.178, p < 0.000), demonstrating that wealthier women had a disproportionate advantage. The pro-rich inequality in utilization was more pronounced in the urban (CI = 0.125) than rural (CI = 0.049) areas. Awareness was distributed almost equitably in rural areas (CI = −0.007, p = 0.165) but showed significant pro-rich inequality in urban settings (CI = 0.014, p < 0.016). Conclusion Uganda’s cervical cancer screening services demonstrate significant vertical inequity, disproportionately favoring wealthier and urban women rather than being allocated according to greater need. To achieve elimination goals, deliberate policies must prioritize resource allocation and awareness for the poorer and rural women who bear the highest burden.